Elastic-Plastic Analysis of Underground Openings by Finite Element Method - Reyes, Salvador F.; Deere, Don U. (Philippine Engineering Journal; Vol 31 No 1 (2010), 2021)
No Abstract. Foreword by Dr. Mark Albert H. Zarco